Use of response surface methodology to evaluate the reducing power in binary solutions of ascorbic acid with natural polyphenolic antioxidants - Marie Aoun; Dimitris P Makris (International Journal of Food Studies)
Natural polyphenols, ferulic acid (FA) and hesperetin (Hp) were tested for their Fe3+-reducing power, using the TPTZ methodology, as a first step to rank them according to their antioxidant potential. Ranking also included quercetin (Qt), a very well-studied natural, polyphenolic antioxidant, and ascorbic acid (AA). All phenolics considered were also tested in binary mixtures with AA, to illustrate possible mixture effects. By employing a simple linear regression approach, combinations of AA / Qt and AA / Hp were shown to result in antagonistic effects, whereas in mixtures of AA / FA, synergism was observed. To thoroughly investigate the role of the relative concentrations of the antioxidants, a 3×3 factorial design was implemented. This approach enabled the recording of the response (reducing power) upon simultaneous variation of concentrations of both antioxidants in the mixtures, and revealed only antagonism for every combination tested. It is proposed that in similar investigations factorial designs need to be implemented for reliable prediction of the antioxidant response(s) within appropriate limits. This is particularly crucial for antioxidants that are destined to be added in food matrices, where maximal antioxidant protection is always sought.